Detection of ABCB5 tumour antigen‐specific CD8+ T cells in melanoma patients and implications for immunotherapy - Borchers, Sylvia; Nowak, Yvonne; Umansky, Viktor; Utikal, Jochen (Clinical & experimental immunology, 2018)
ATP binding cassette subfamily B member 5 (ABCB5) has been identified asa tumour-initiating cell marker and is expressed in various malignancies,including melanoma. Moreover, treatment with anti-ABCB5 monoclonalantibodies has been shown to inhibit tumour growth in xenotransplantationmodels. Therefore, ABCB5 represents a potential target for cancerimmunotherapy. However, cellular immune responses against ABCB5 inhumans have not been described so far. Here, we investigated whetherABCB5-reactive T cells are present in human melanoma patients and testedthe applicability of ABCB5-derived peptides for experimental induction ofhuman T cell responses. Peripheral blood mononuclear cells (PBMNC)isolated from blood samples of melanoma patients (n540) were stimulatedwith ABCB5 peptides, followed by intracellular cytokine staining (ICS) forinterferon (IFN)-gand tumour necrosis factor (TNF)-a. To evaluateimmunogenicity of ABCB5 peptides in naive healthy donors, CD8 T cellswere co-cultured with ABCB5 antigen-loaded autologous dendritic cells(DC). ABCB5 reactivity in expanded T cells was assessed similarly by ICS.ABCB5-reactive CD81T cells were detectedex vivoin 19 of 29 patients,melanoma antigen recognised by T cells (MART-1)-reactive CD81T cells insix of 21 patients. In this small, heterogeneous cohort, reactivity againstABCB5 was significantly higher than against MART-1. It occurredsignificantly more often and independently of clinical characteristics.Reactivity against ABCB5 could be induced in 14 of 16 healthy donorsinvitroby repeated stimulation with peptide-loaded autologous DC. AsABCB5-reactive CD8 T cells can be found in the peripheral blood ofmelanoma patients and an ABCB5-specific response can be inducedin vitroin naive donors, ABCB5 could be a new target for immunotherapies inmelanoma.
Im Titel ist die Zahl "5" tief- und das Zeichen "+" hochgestellt
First published: 23 September 2017
Gesehen am 02.04.2020